Revue des Deux Mondes (Paris)
"Bibliotheek E. AnseelePeriodiciteit: tweewekelijksHoofdredactie: René Doumio (directeur-gérant)Redactie: L. Bertrand (de l'Académie française), C.J. Diamandy, André Maurois, Edith Wharton, Paul Hazard, Maurice Levaillant, Victor Forlin, André Gavoty, René Doumic, René PinonBeheer/Administratie: rue de l'Université 15, Paris-7eDrukker/Drukkerij: Typ. Philippe Renouard, rue des Saints-Pères 19, Paris"